SISTEM EKONOMI ISLAM: Dialektika Antara Thesis, Antitesis dan Plagiatis (IAIN Tulungagung, 2015)
Discourses in Islamic economic system are not new in economic study. There is always a big question behind Islamic economic system, what makes Islamic economic system with capitalism economic system and socialism economic system different! Historically, Moslems had explained earlier before middle century then developed by modern economic theorist. Al Qur’an and Al Hadits have explained how a Moslem must undertake two orientation in his economic activity, there are material orientation and religious orientation. Religious orientation that will be a Moslem can be justful in economic capitalism practice. Even if Moslem has a claim to property but every Moslem is very aware if his property is just a mandate and in property have right a poor and he must distribute zakat/ sadaqah mechanism. Because, zakat/ sadaqah is a social responsibility for a Moslem. so, Islamic economic system look from historical and conceptual view based on al Qur’an and al Hadits that have strong fundamental, so Islamic economic system is believed to be same with conceptual capitalism economic system and socialism economic system. Keyword: Islam Economy System, Zakat, capitalism economic